A Contingency Theory of Socialization - Feldman, Daniel Charles (Administrative Science Quarterly, 1976)
September 1976, volume 21 A model of individual socialization into organizations is presented and tested. The model (a) identifies three distinct stages of socialization, (b) specifies the activities engaged in by an individual at each stage, and (c) specifies the personal and organizational contingencies that control an individual's movement through the stages. Interview and questionnaire data collected from 118 hospital employees -nurses, nurse's aides, radiology technologists, tradesmen, and accounting clerks -were used to develop, refine, and test the model. The model basically was supported by the data. Four variables are identified as possible outcomes of the socialization process: general satisfaction, mutual influence, internal work motivation, and job involvement. Two of these variables general satisfaction and mutual influence are empirically linked with important aspects of the socialization process, and are shown to increase steadily as individuals progress through socialization. The differences between the socialization experiences of professional, paraprofessional, and nonprofessional workers are identified and explained, and implications for the conduct of socialization programs are drawn.1